2017
DOI: 10.1002/oby.22028
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Eating Disorder Pathology are Associated with Weight Change in Family‐Based Behavioral Obesity Treatment

Abstract: Objective Children with overweight/obesity have elevated eating disorder (ED) pathology, which may increase their risk for clinical EDs. The current study identified patterns of ED pathology in children with overweight/obesity entering family-based behavioral weight loss treatment (FBT), and examined whether children with distinct patterns differed in their ED pathology and zBMI change across FBT. Methods Before participating in 16-session FBT, children (N=241) completed surveys/interviews assessing ED patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…These results contribute to the literature by further evaluating FBT, the current recommended treatment for childhood obesity. Consistent with Balantekin et al (), this study shows that ED symptoms did not increase immediately following treatment. This study extended upon previous research to demonstrate symptoms did not increase, and in fact decreased, in several domains through 6 months following treatment and 18 months following treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results contribute to the literature by further evaluating FBT, the current recommended treatment for childhood obesity. Consistent with Balantekin et al (), this study shows that ED symptoms did not increase immediately following treatment. This study extended upon previous research to demonstrate symptoms did not increase, and in fact decreased, in several domains through 6 months following treatment and 18 months following treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The results in this study support previous research that pediatric behavioral weight‐loss treatment does not appear to exacerbate ED symptomatology (Balantekin et al, ; Butryn & Wadden, ; Carter & Bulik, ; Epstein, Paluch, Saelens, Ernst, & Wilfley, ; Hayes et al, ). These results contribute to the literature by further evaluating FBT, the current recommended treatment for childhood obesity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Three studies did not report on personnel involved in intervention delivery. Parental involvement was reported as part of the intervention in 50 studies …”
Section: Resultsmentioning
confidence: 99%
“…The change in body image between pre‐intervention and postintervention was reported in 27 studies, between pre‐intervention and follow‐up in three studies, and 13 studies reported data at all three time points. Of the 40 studies reporting body image pre‐intervention and postintervention ranging in duration from 2 weeks to 24 months, body image was reported to be significantly improved compared with baseline in 22 studies, not significantly changed in 10 studies, five studies did not state whether or not the change was significant and three studies reported a significant improvement in one body image measure and no change in another.…”
Section: Resultsmentioning
confidence: 99%